Modifikasi Restorasi Stainless Steel Crown Pada Kasus Severe Early Childhood Caries - Yoana Yoana; Inne Suherna Sasmita (Jurnal Material Kedokteran Gigi, 2019)
Early Childhood Caries (ECC) is a form of dental caries that occur rapidly. ECC is a common chronic disease in children that could harm self-esteem, nutrition, oral cavity development, also quality of life, then veer to malocclusions and psychological problems. In children with severe early childhood caries (SECC), losing vertical dimension of occlusion were also reported to occur 2.5 times more. Restoration of deciduous teeth with severe damage offers great challenge for pediatric dentists. This case reported clinical management of patients suffering from SECC using stainless steel crown to restore masticatory function and vertical dimensions. A 5-year-old boy escorted by his parents came to pedodontic dentistry Clinic at Universitas Padjadjaran Dental and Oral Hospital, with complaints of many tooth were damage. On clinical examination, it was shown that all primary teeth have caries, except for the two mandibular lateral incisor, teeth 16 and 26 were partial eruption, with deep bite in the anterior region. Therefore the diagnosis was deep bite in the anterior region because of SECC. Correction then had done by modifying metal crown restorations on posterior teeth. Modification of stainless steel crown restoration can correct vertical dimension of occlusion so as to prevent malocclusion.